Synthesis of cycloalkyl substituted purine nucleosides via a metal-free radical route. Issue 18 (21st April 2016) - Wang, Dong-Chao; Xia, Ran; Xie, Ming-Sheng; Qu, Gui-Rong; Guo, Hai-Ming
Abstract : The selective synthesis of C6-monocycloalkyl or C6, C8-dicycloalkyl substituted purine nucleosides could be realized. Furthermore, uracil and related nucleosides were also suitable substrates, giving the C5-cyclohexyl substituted uracil derivatives in good yields with excellent regioselectivities. Abstract : An efficient route to synthesize cycloalkyl substituted purine nucleosides was developed. This metal-free C–H activation was accomplished by a t BuOO t Bu initiated radical reaction. By adjusting the amount of t BuOO t Bu and reaction time, the selective synthesis of C6-monocycloalkyl or C6, C8-dicycloalkyl substituted purine nucleosides could be realized. Furthermore, uracil and related nucleosides were also suitable substrates, giving the C5-cyclohexyl substituted uracil derivatives in good yields with excellent regioselectivities.